Medicinal plants as alternative for control of livestock parasites. 2. Protozoa - CHHABRA, M B; PATHAK, K M L; MURALEEDHARAN, K (The Indian Journal of Animal Sciences, 2014)
Antiparasitic agents have been used since long to combat the problem of parasites, both internal and external. But the emergence of resistance against industrial products, particularly in gastro-intestinal parasites including coccidia and in ectoparasites, has resulted in search for alternative control strategies. The application of ethnoveterinary practices and harnessing of plants as anthelmintics, anticoccidials and acaricidal agents is gaining popularity worldwide. Natural substances have a long record of safety for man, animals and environment. An increasing number of them are now proving their therapeutic value universally. The acceptability of plant products as alternatives depends largely on their scientific validation. A large number of studies in India and elsewhere have provided evidence for presence of bioactive components through in vitro, in vivo and clinical screening of plants. The target parasites include all major groups but this review is intended to deal with protozoans. Antiprotozoal activities has been identified in several plant products. They are now providing alternative means for combating some of the economically important livestock diseases with limited existing therapeutic options. Anti-trypanosomal potential was observed in several plants and bioactive compounds sourced from plants have exhibited antioxidant, immuno-modulatory and growth-promoting effects in addition to direct coccidia-suppression, thereby brightening their prospects as replacements for commercial anti-coccidial drugs for poultry. Plant-based agents as components of an integrated approach for the management of several important parasites, are increasingly finding favour.